2020
DOI: 10.3389/fgene.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Assessment of Genetic Variation and Population Distinctiveness of the Pig Family in South Africa

Abstract: Genetic diversity is of great importance and a prerequisite for genetic improvement and conservation programs in pigs and other livestock populations. The present study provides a genome wide analysis of the genetic variability and population structure of pig populations from different production systems in South Africa relative to global populations. A total of 234 pigs sampled in South Africa and consisting of village (n = 91), commercial (n = 60), indigenous (n = 40), Asian (n = 5) and wild (n = 38) populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 140 publications
(90 reference statements)
2
20
0
1
Order By: Relevance
“…The first suggestive pleiotropic region on BTA19 (27.0–28.0 Mb) contains four genes that may play important regulatory functions in metabolism and gene expression: Dynein Axonemal Heavy Chain 2 ( DNAH2 ), Chromodomain Helicase DNA Binding Protein 3 ( CHD3 ), Arachidonate 15-Lipoxygenase Type B ( ALOX15B ), and Phosphoribosylformylglycinamidine Synthase ( PFAS ). The DNAH2 gene codes for a motor protein found in cilia and flagella that was related to intramuscular fat content and carcass weight in pigs ( Hlongwane et al, 2020 ). The CHD3 protein deacetylates histones for chromatin remodeling and may have an important regulatory function.…”
Section: Resultsmentioning
confidence: 99%
“…The first suggestive pleiotropic region on BTA19 (27.0–28.0 Mb) contains four genes that may play important regulatory functions in metabolism and gene expression: Dynein Axonemal Heavy Chain 2 ( DNAH2 ), Chromodomain Helicase DNA Binding Protein 3 ( CHD3 ), Arachidonate 15-Lipoxygenase Type B ( ALOX15B ), and Phosphoribosylformylglycinamidine Synthase ( PFAS ). The DNAH2 gene codes for a motor protein found in cilia and flagella that was related to intramuscular fat content and carcass weight in pigs ( Hlongwane et al, 2020 ). The CHD3 protein deacetylates histones for chromatin remodeling and may have an important regulatory function.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the results reported in our study suggested that the explanatory power of the SNPs is slightly lower; this could be justified by the fact that local indigenous breeds have not been considered for design of commercial porcine chip. This could be indicated by the results of Hlongwane et al, who reported the genetic variation and population distinctiveness of three commercial, four village, two indigenous, three wild, and one Asian pig breeds [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using literature on East African pigs and phenotypic characteristics of pigs owned by the smallholder farmers in the study area (Figure 2), we chose as putative ancestral populations, Asian, Duroc, British, Iberian, and Continental European pig breeds. We explored the ancestry of Uganda pigs in global context by incorporating publicly or privately available genotypes from the putative ancestral populations (Cleveland et al, 2012;Yang et al, 2017;Pena et al, 2019;Pfeiffer et al, 2019;Hlongwane et al, 2020).The data were merged and manipulated in PLINK1.9 (Chang et al, 2015). Prior to merging the data, the SNP positions in each dataset were updated to the sus scrofa reference 11.1 genome build (Illumina, 2013).…”
Section: Animals and Genotyping Datamentioning
confidence: 99%